Virtual Reality in Education - Sadiku, Matthew N. O.; Sadiku, Janet O.; Chukwu, Uwakwe C. (Researchparks Publishing, 2023)
Virtual reality is a human-designed system with the help of computer and electronic devices such as cameras and sensors to interact with 3-D environments. Many challenges that educators face in online teaching can be addressed by using VR. VR can provide learners with an immersed environment where otherwise students cannot access. VR is an exciting way for turning ordinary classrooms into places of wonder, inquiry, and adventure. VR increases student's engagement and interest in learning. It makes many hard topics easy by 360-degree realistic view. This paper provides an introduction to virtual reality.